Mechanisms of survival, responses and sources of Salmonella in low-moisture environments - Finn, Sarah; Condell, Orla; McClure, Peter; Amézquita, Alejandro; Fanning, Seamus (Frontiers in Microbiology, 2013)
Some Enterobacteriaceae possess the ability to survive in low-moisture environments for extended periods of time. Many of the reported food-borne outbreaks associated with low-moisture foods involve Salmonella contamination. The control of Salmonella in low-moisture foods and their production environments represents a significant challenge for all food manufacturers. This review summarises the current state of knowledge with respect to Salmonella survival in intermediate- and low-moisture food matrices and their production environments. The mechanisms utilised by this bacterium to ensure their survival in these dry conditions remain to be fully elucidated, however in depth transcriptiomic data is now beginning to emerge regarding this observation. Earlier research work described the effect(s) that low-moisture can exert on the long-term persistence and heat tolerance of Salmonella, however, data are also now available highlighting the potential cross-tolerance to other stressors including commonly used microbicidal agents. Sources and potential control measures to reduce the risk of contamination will be explored. By extending our understanding of these geno- and phenotypes, we may be able to exploit them to improve food safety and protect public health.